Rancang Bangun Sistem Absensi Fingerprint dan Monitoring Siswa Berbasis Web Menggunakan ESP32 di SMK Negeri 1 Tangerang Selatan - Muhamad Nur Wahid; Mohamad Mulqi Arif; Muhammad Agiel Priautama; Sutriyono Sutriyono (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Background: Student attendance recording at SMK Negeri 1 Tangerang Selatan was previously conducted manually and later using QR Code, yet both methods were prone to misuse, including proxy attendance and the sharing of codes outside the school premises, resulting in attendance data that did not reflect actual conditions. Objective: This study aims to design and build a fingerprint-based student attendance system using the ESP32 microcontroller integrated with a web-based monitoring system at SMK Negeri 1 Tangerang Selatan. Methods: This study employed the Research and Development (R&D) method with a System Development Life Cycle (SDLC) Waterfall approach, covering requirements analysis, system design (UML modeling including use case, activity, sequence, and class diagrams, as well as hardware design), coding, implementation, and Black Box Testing. Results: Test results show that all main system functions operate as designed: the AS608 fingerprint sensor is able to recognize registered students' fingerprints and reject unregistered ones, the ESP32 successfully transmits attendance data to the server via WiFi, data is stored in a MySQL database and can be displayed in real time on a web monitoring dashboard accessible to admins and teachers with different access rights. Suggestion: Further development is needed, such as automatic notifications to parents, integration with academic databases, and long-term testing to assess system stability in real school conditions.